Pengaruh Modal dan Harga Barang Terhadap Pendapatan Usaha Bengkel Mobil Sekawan Motor di Kota Karawang - Octaviani, Haniifah; Isyanto, Puji (Nanggroe: Jurnal Pengabdian Cendikia, 2024)
This research aims to analyze the influence of capital and goods prices on the business income of the Sekawan Motor car repair shop in Karawang City. Sufficient capital and setting the right price for goods are key factors in increasing the income and profitability of a car repair shop business. The research method used is a quantitative approach with data collection through questionnaires, interviews and documentation. The results of data analysis using regression show that business capital has a significant positive influence on car repair shop business income. On the other hand, the price of goods is not proven to have a significant effect on income. Thus, car repair business owners need to pay attention to good capital management and appropriate pricing strategies in order to improve the financial performance of the repair shop business. The conclusion of this research emphasizes the important role of capital and the price of goods in determining the income of a car repair shop business.